Racism and Structural Violence: Interconnected Threats to Health Equity - Sharif, Mienah Zulfacar; García, Jennifer J.; Mitchell, Uchechi; Dellor, Elinam D.; Bradford, Natalie J.; Truong, Mandy (Frontiers in Public Health, 2022)
In 2020, the continuing murder of Black Americans by police officers received widespread media attention and sparked global outrage. Public health responses to these events focused on discrimination by police and structural racism in broader society. However, police violence is but one of many forms of racialized violence propagated by structural racism and anti-Black racism in particular. We aim to expand the current public health dialogue by describing how structural racism and structural violence are deeply interrelated; embedded in institutions, systems, and processes; and threaten health, safety, and well-being across the life course for racialized minority groups. Structural racism and structural violence are threats to health equity and anti-racist public health work.